COMPARATIVE EFFICACY OF CETIRIZINE GENERIC (MANUFACTURED BY EGIS, HUNGARY) AND ORIGINAL IN THE FORM OF DROPS IN COMPLEX TREATMENT OF ATOPIC DERMATITIS IN INFANTS - I.V. Makarova; O.V. Zhiglinskaya; E.A. Mikhailova; V.G. Sukhorukova ("Paediatrician" Publishers LLC, 2007)
The article compares the efficacy of two medications containing cetirizine in the form of drops in treating atopic dermatitis in 6-24 months old children. It is shown that the use of both medications in complex treatment of atopic dermatitis children helps achieve a fast clinical effect. Cetirizine generic is no less effective than the original one in treatment of atopic dermatitis in children and is well accepted by the patients. Key words: atopic dermatitis, children, treatment, cetirizine.